PELATIHAN PEMBUATAN PAKAN FERMENTASI DAN APLIKASI PROBIOTIK UNTUK ITIK PETELUR DI DESA KEBONSARI SIDOARJO - Dharmawan, Anggi Putra; Putri, Arni Al Hikmah; Nurwahyudi, Mochammad; Afifah, Fifi (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2019)
Kebonsari village is the only one location in Sidoarjo that empowers duck farms. This potential is alsoaccompanied by the presence of livestock wastes, one of which is a bad odor that needs handling. It canbe handled using probiotics, either orally (for food) or sprayed on the cage. The purposes of this dedicationis to find out the level of understanding of Kebonsari villagers, especially ducks breeders on probiotics andimprove the quality of dairy farms in the village Kebonsari seen from the aspects of cleanliness and health.This is due to the lack of knowledge of duck breeders in the area to reduce the smell of cattle dung. Thesteps taken are to socialize the way of making and demonstration and monitoring and evaluation. It wasfound that 80% of breeders have skill in duck feeding, 80% said the smell of dirt was reduced significantly,and 80% said duck health improved. Based on this it can be concluded that probiotics are used effectivelyto reduce the smell of dirt and maintain the health of livestock.